THE Urgensi Ahli Linguistik Forensik Dan Psikologi Forensik Dalam Sistem Peradilan Pidana Terpadu - Yanti Amelia Lewerissa (LUTUR Law Journal, 2023)
The existence of information from forensic linguistics experts and forensic psychology experts is very much needed by law enforcement officers in the criminal justice system. to make light of a crime. The purpose of this study was to analyze the role of forensic linguistics and forensic psychology experts in helping law enforcement officers to seek and find the truth in order to make light of a crime. The research method used in this research is normative legal research which is complemented by social legal research. The approach used is a statutory approach and a conceptual approach. Data collection technique is literature study and analyzed qualitatively. The results showed that information from forensic linguistics experts and forensic psychologists could be requested from the start of the investigation phase even if required by the judge, forensic linguistics and forensic psychology experts could be presented in the trial process either by the public prosecutor or by the defendant's legal counsel, whose main purpose is assist law enforcement officers to make light of a crime. Thus, the existence of information from forensic linguistics and forensic psychology experts is very much needed in an integrated criminal justice system. However, there are some limitations such as lack of human resources, lack of legal knowledge possessed by experts, conflicts of interest and differences in paradigms from experts even though they have the same specifications are some of the obstacles that are often faced by law enforcement officers when faced with situations that require the role of an expert.